2019
DOI: 10.1039/c8cc10021g
|View full text |Cite
|
Sign up to set email alerts
|

Double-headed nanosystems for oral drug delivery

Abstract: We demonstrate a novel strategy to engineer double-headed nanosystems by chemical modification of the carboxyl terminal polyester with a linker that offers tripodal arrangement of ligands on the particle surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…The literature suggests that TfR is widely expressed in the blood-ocular barriers and can potentially be useful for active delivery across these barriers ( 24 ). In addition, our ex vivo and in vivo data support the role of TfR in transport across the blood-ocular barriers ( 22 , 25 ). Here, we report the efficacy of oral CUR aided by double-headed nanoparticles in a model of lens-induced uveitis that mimics the intraocular inflammation seen after cataract surgery.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…The literature suggests that TfR is widely expressed in the blood-ocular barriers and can potentially be useful for active delivery across these barriers ( 24 ). In addition, our ex vivo and in vivo data support the role of TfR in transport across the blood-ocular barriers ( 22 , 25 ). Here, we report the efficacy of oral CUR aided by double-headed nanoparticles in a model of lens-induced uveitis that mimics the intraocular inflammation seen after cataract surgery.…”
Section: Introductionsupporting
confidence: 73%
“…We have selected PLGA-GA 2 nanoparticles as a vehicle for the delivery of CUR because of its ability to navigate across the intestinal barriers via the TfRs in a noncompetitive manner (independent of transferrin-binding sites), resulting in improved oral bioavailability of CUR ( 21 , 22 ). The optimized synthesis protocols ( Fig, 1A ) led to scalable quantities of PLGA-GA 2 in which the GA coupling was confirmed by nuclear magnetic resonance (NMR), characterized by amide bond formation [8.01 parts per million (ppm)] and doublets at 5.7 and 6.7 ppm for GA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this limitation, our laboratory recently reported the use of gambogic acid (GA), known for its affinity to transferrin receptors, independent of transferrin binding (Kasibhatla et al, 2005), as a noncompetitive ligand for TfR present in the small intestine (Saini et al, 2016;Ganugula et al, 2017a). The GA modified poly (lactic-coglycolic acid) nanoparticles demonstrated noncompetitive transport in cellulo and improved oral bioavailability of encapsulated drugs or drug-like compounds (e.g., cyclosporine, curcumin, and insulin) in rodents (Saini et al, 2016;Ganugula et al, 2017a;Kaur et al, 2019). Our laboratory also observed that the ligand-receptor stoichiometry plays an important role in receptor-mediated drug delivery.…”
Section: Nanosystemsmentioning
confidence: 99%